Penyuluhan Tentang Pentingnya Inovasi dan Kemasan dalam Penerapan Digital Marketing di Era Revolusi Industri 4.0 pada UMKM di Desa Ngepoh - Larissa Diva Nabilah; Sonja Andarini (Fakultas Teknik Universitas Cenderawasih, 2023)
Utilizing digital marketing in the industrial era 4.0 can become a new strategy in product marketing activities, by making it easier for businesses to monitor and provide for the needs and wants of potential consumers. On the consumer side, digital marketing is a medium that can make it easier to find a product. Ngepoh Village, Dringu District, has a lot of potential, including in the economic sector. This can be seen from the many MSMEs operating in Ngepoh Village. However, their marketing efforts are still limited and use conventional methods. Therefore, MSMEs in this village need training on the importance of utilizing digital marketing so that their marketing system can be improved. The aim of this counseling is to help MSMEs reach a wider market and increase their sales. In its implementation, this activity uses two methods, namely socialization regarding digital marketing and assistance in upgrading the packaging of MSME players. In socialization activities include product introduction, marketing strategy, and packaging design. The approach used involves training in the form of socialization and tutorials on creating accounts on digital platforms and managing digital media. The results of this activity suggest the need to provide regular guidance in order to optimize digital marketing strategies and increase MSME business sales. With ongoing assistance, it is hoped that MSMEs can continue to take advantage of the potential of digital marketing in an effective and sustainable manner to achieve success in marketing their products